RELATION BETWEEN STANDERD PENETRATION TEST AND SKIN RESISTANCE OF DRIVEN CONCRETE PILE IN OVER CONSOLIDATED CLAY SOIL (Journal of Engineering, 2011)
In this research the relation between skin resistances and standard penetration test of over consolidatedclay soils has been studied. The research includes doing boreholes at Babil governorate in Iraq to getundisturbed samples and standard penetration test. Determination skin friction from direct shear test betweensmooth concrete and soil was explored in laboratory for design purposes and correlated with standardpenetration test values. In many foundation design problems, the shear strength between soil andfoundation materials were estimated or correlated without any direct methods for measurement.Twelve strain controlled direct shear tests were performed simulate the shear strength interactionbetween smooth concrete and undisturbed over consolidated silty clay, determine the soil – foundationinterface friction, considering the following variables :(1) over consolidation ratio OCR between 1.4 to2.4 (2) Concrete, smooth surface, (3) Undisturbed samples, (4) Variation of the normal load between thefriction surface. The results showed that both cohesion and internal friction should be considered inevaluating skin friction. The results of cohesion and angle of internal friction were correlate with thestandard penetration test SPT –N . Interface friction angle was 14.5° , while the adhesion was 15.5 kPa.The ultimate shear strength was mobilized through 10%- 16% strain in the direction of shear surface. .A fairly good correlation between the N70-value and the interface friction parameters were establishedfor determination unit skin friction for driven piles. Finally, based on the test results, a simple relation wasproposed to relate the N70 value and interface friction of silty clay soils for a range of N70 between 12 and 20.